Vicarious warfare and dynamic efficiency of companies in the aerospace and defence industry - Nourani, Mohammad; Lu, Wenmin; Irene, Wei Kiong Ting (John Wiley & Sons, Ltd., 2020)
This study explores the economic performance that vicarious warfare can bring for the aerospace and defence industry. First, this study measures the performance of 22 companies using a nonradial dynamic data envelopment analysis model from 2011 to 2017. Second, this study evaluates whether vicarious warfare can influence the performance. The efficiency analysis suggests rooms for improvements meanwhile, the projection analysis suggests that market value should be significantly increased, and the number of employees should be reduced significantly. The regression analysis suggests that the number of times a country takes a side in wars would positively affect the efficiency of companies.